Diagnosis and management of restless legs syndrome in children - Simakajornboon, Narong (2009)
Recent published evidence suggests that restless legs syndrome (RLS) and periodic limb movement disorder (PLMD) are common condition in children and adolescents. It is likely that if left untreated, RLS and PLMD may lead to adverse cardiovascular and neurocognitive consequences. However, the diagnosis of RLS and PLMD in children is challenging, particularly because children are relatively unable to describe typical RLS symptoms. The International Restless Legs Study Group has recently published consensus criteria for the diagnosis of RLS and PLMD in children. In addition to clinical description of RLS symptoms, supportive evidence including the presence of clinical sleep disturbances, documented periodic limb movements in sleep from overnight sleep study and family history of restless legs syndrome may be required. Few if any controlled studies have addressed the management of RLS and PLMD, which may involve both non-pharmacologic and pharmacologic approaches. In this context, the importance of avoidance of aggravating factors and good sleep hygiene cannot be overemphasized. Children with evidence of low-iron storage, i.e., low-serum ferritin and/ or iron levels may likely benefit from iron therapy. While there is overall limited experience regarding the use of dopaminergic agents in children with RLS and PLMD, published reports suggesting efficacy of compounds such as levodopa, ropinirole, pramipexole and pergolide have emerged. Other medications including benzodiazepine, anti-convulsants, alpha-adrenergic and opioid medications have not been adequately studied in children. Children with RLS and PLMD should have regular follow-up visits to evaluate clinical improvement and to monitor adverse effects from the selected therapy. Based on aforementioned findings, it is clear that a substantial research effort is needed to evaluate the pathophysiology,